ATIM-38. PHASE 2 STUDY TO EVALUATE THE CLINICAL EFFICACY AND SAFETY OF MEDI4736 (DURVALUMAB, DURVA) + BEVACIZUMAB (BEV) IN BEV-NAÏVE PATIENTS WITH RECURRENT GLIOBLASTOMA (GBM). (5th November 2018) - Reardon, David; Kaley, Thomas; Dietrich, Jorg; Clarke, Jennifer; Dunn, Gavin; Lim, Michael; Cloughesy, Tim; Gan, Hui; Park, Andrew; Schwarzenberger, Paul; Ricciardi, Toni; Macri, Mary; et al.
Abstract: BACKGROUND: Durva is a human IgG1 mAb against PD-L1. Blockade of PD-1/PD-L1 has shown benefit among solid tumors; data implicate PD-1/PD-L1 signaling as a significant contributor to immunosuppression in GBM. BEV is an approved angiogenesis inhibitor for recurrent GBM; angiogenesis inhibition may promote antitumor benefit of immunotherapies. A review showed that lower dose BEV resulted in longer PFS/OS than the standard. METHODS: Ongoing Phase 2 open-label study (NCT02336165) evaluates safety and efficacy of durva (10mg/kg Q2W) in 5 GBM cohorts. Results are presented for Cohorts B2 (durva + BEV 10mg/kg Q2W) and B3 (durva +BEV 3mg/kg Q2W) in BEV-naïve recurrent GBM. Primary efficacy endpoint for Cohorts B2/B3 is 6-month progression-free survival (PFS6), by modified RANO per investigator assessment; secondary endpoints include safety/tolerability. Comparative benchmark for BEV in recurrent GBM is PFS6 of 42%. The null hypothesis (PFS6 ≤42%) was tested in Intent-to-Treat (ITT) population against the alternative hypothesis (PFS6 ≥62%). ITT includes patients receiving any dose of durva and having at least baseline and 1 post-baseline tumor assessment. Durva alone in Cohort B of this study demonstrated PFS6 of 20% (90% CI: 9.7, 33.0). RESULTS: As of 02Apr2018, 33 patients were treated in each cohort (B2, male: 54.5%, median age: 57.0 [40–74] years; B3, male: 60.6%, median age: 54.0 [23–73] years). Most common treatment-related adverse events (TRAEs, in ≥4 [12.1%] patients in either cohort): fatigue, dysphonia, increased ALT, AST, amylase, or lipase, diarrhea, hypertension, arthralgia, headache, and proteinuria. Incidences of TRAEs by maximum CTCAE grade (Gr) ≥3 for Cohorts B2/B3 were Gr3: 24.2/6.1%; Gr4: 0/6.1%; and Gr5: 0/0%. Kaplan-Meier estimate for PFS6 (n=33 each): B2, 15.2% (80% CI: 8.2, 24.0); B3, 21.1% (80% CI: 12.4, 31.4); 3 patients in each cohort showed partial response. CONCLUSIONS: The addition of durva to BEV did not improve on the outcome of durva alone.